INTERNALIZATION OF THE VALUE OF CARING FOR THE ENVIRONMENT IN CHILDREN THROUGH ISLAMIC RELIGIOUS EDUCATION IN FAMILIES OF THE COASTAL COMMUNITIES OF BATUBARA REGENCY - Mukhtar, Ghazali (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the process of internalizing the value of caring for the environment in children through Islamic Religious Education in coastal community families. The research was conducted in Pahlawan Village, Tanjung Tiram District, Batubara Regency. The method used in this study is a descriptive qualitative approach. The results of the study show that the process of internalizing the value of caring for the environment in children is carried out through Islamic Religious Education in coastal community families carried out through verbal communication methods by parents to children through stories and direct advice and by providing good examples in everyday life.